2019
DOI: 10.1063/1.5115342
|View full text |Cite
|
Sign up to set email alerts
|

Nanoscale aluminum plasmonic waveguide with monolithically integrated germanium detector

Abstract: Surface plasmon polaritons have rapidly established themselves as a promising concept for molecular sensing, near-field nanoimaging, and transmission lines for emerging integrated ultracompact photonic circuits. In this letter, we demonstrate a highly compact surface plasmon polariton detector based on an axial metal-semiconductor-metal nanowire heterostructure device. Here, an in-coupled surface plasmon polariton propagates along an aluminum nanowire waveguide joined to a high index germanium segment, which e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 31 publications
0
19
0
Order By: Relevance
“… 29 As previously shown, for such a configuration, we experimentally determined a SPP propagation length of L SPP = 140 nm at λ = 532 nm for 40 nm thin c-Al NWs. 29 With respect to the actual device geometry, Finite Difference Time Domain (FDTD) simulations revealed that adding the omega-shaped gate atop the Al–Ge nanojunction significantly lowers the LSPP (see Figure S1 ).…”
Section: Resultsmentioning
confidence: 69%
See 3 more Smart Citations
“… 29 As previously shown, for such a configuration, we experimentally determined a SPP propagation length of L SPP = 140 nm at λ = 532 nm for 40 nm thin c-Al NWs. 29 With respect to the actual device geometry, Finite Difference Time Domain (FDTD) simulations revealed that adding the omega-shaped gate atop the Al–Ge nanojunction significantly lowers the LSPP (see Figure S1 ).…”
Section: Resultsmentioning
confidence: 69%
“…Effective surface plasmon excitation is achieved by coupling normal incident TM polarized laser with a vacuum wavelength of λ = 532 nm into the c-Al NW waveguide using a Si 3 N 4 membrane FGC, located above the Al contact pad (see Figure a,b) . As previously shown, for such a configuration, we experimentally determined a SPP propagation length of L SPP = 140 nm at λ = 532 nm for 40 nm thin c-Al NWs .…”
Section: Resultsmentioning
confidence: 81%
See 2 more Smart Citations
“…Novel approaches enabling efficient ways to create photo-voltages, range from 2D material plasmonic hybrid structures [1][2][3] over metal-insulator-metal waveguides [4,5] to semiconductor/metal nanowire junctions [6]. One of the most widely studied systems for hot-carrier based photodetection however, are common semiconductor(SC)/metal junctions.…”
Section: Introductionmentioning
confidence: 99%